Effects of reinforcer probability, delay, and response requirements on the choices of rats and pigeons: Possible species differences - Mazur, James E (Journal of the Experimental Analysis of Behavior, 2005)
In Experiment 1 with rats, a left lever press led to a 5-s delay and then a possible reinforcer. A right lever press led to an adjusting delay and then a certain reinforcer. This delay was adjusted over trials to estimate an indifference point, or a delay at which the two alternatives were chosen about equally often. Indifference points increased as the probability of reinforcement for the left lever decreased. In some conditions with a 20% chance of food, a light above the left lever was lit during the 5-s delay on all trials, but in other conditions, the light was only lit on those trials that ended with food. Unlike previous results with pigeons, the presence or absence of the delay light on no-food trials had no effect on the rats' indifference points. In other conditions, the rats showed less preference for the 20% alternative when the time between trials was longer. In Experiment 2 with rats, fixed-interval schedules were used instead of simple delays, and the presence or absence of the fixed-interval requirement on no-food trials had no effect on the indifference points. In Experiment 3 with rats and Experiment 4 with pigeons, the animals chose between a fixed-ratio 8 schedule that led to food on 33% of the trials and an adjusting-ratio schedule with food on 100% of the trials. Surprisingly, the rats showed less preference for the 33% alternative in conditions in which the ratio requirement was omitted on no-food trials. For the pigeons, the presence or absence of the ratio requirement on no-food trials had little effect. The results suggest that there may be differences between rats and pigeons in how they respond in choice situations involving delayed and probabilistic reinforcers.
Keywords: *Behavior, Animal/ph [Physiology]; *Choice Behavior; *Reaction Time; *Reinforcement, Psychology; Animals; Behavior, Animal; Choice; Choice Behavior; Columbidae; Delay; Fixed interval; Fixed ratio; Key peck; Lever press; Male; Pigeons; Probability; Rats; Rats, Sprague-Dawley; Reaction Time; Reinforcement (Psychology); Species Specificity; Sprague Dawley rat; animal; animal behavior; decision making; dept.psy; male; peer-reviewed; physiology; pigeons and doves; probability; rat; reaction time; reinforcement; review; species difference